Enhancement of External Quantum Efficiency of GaSb/GaAs solar cell Based on Graphene - Shafie, S; Imanie, M (International Journal of Computer Sciences and Engineering, 2025)
The main limitations of the typical solar conversion device is that low energy photons cannot excite charge carriers to the conduction band, therefore do not contribute to the device’s current, and high energy photons are not efficiently used due to a poor match to the energy gap. Currently, Graphen based Solar Cells GBSC are one of the most active research fields in the third generation solar cells which can resolve this problem. In the present work, we are interested in modeling and simulating of both standard GaAs p-i-n solar cell and GaSb/GaAs Graphene Solar Cell. When comparing 40-layers GaSb/GaAs Graphene solar cell with standard GaAs solar cell, the conversion efficiency in simulation results increased from 16.48 % to 22.46 %, which is relatively 36.3% increase. Also, the absorption range edge of photons with low energies extended from 900 to 1200 nm. The results reveal that the GaSb/GaAs Graphene solar cell manifests much larger power conversion efficiency than that of p-i-n junction solar cells.